2022
DOI: 10.5713/ab.21.0504
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for frozen-thawed sperm motility in stallions across various horse breeds

Abstract: Objective:The semen quality of stallions including sperm motility is an important target of selection as it has a high level of individual variability. However, effects of the molecular architecture of the genome on the mechanisms of sperm formation and their preservation after thawing have been poorly investigated. Here, we conducted a genome-wide association study (GWAS) for the sperm motility of cryopreserved semen in stallions of various breeds.Methods: Semen samples were collected from the stallions of 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Herewith, breed may have very little effect on sperm morphology, possibly due to high inbreeding in small breeds. For example, our previous study [3] also showed little influence of breed on sperm morphology. Abnormal sperm morphology can reduce the chances of fertilization [12] and embryo development; it can also increase the risk of transmitting genetic defects [13].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Herewith, breed may have very little effect on sperm morphology, possibly due to high inbreeding in small breeds. For example, our previous study [3] also showed little influence of breed on sperm morphology. Abnormal sperm morphology can reduce the chances of fertilization [12] and embryo development; it can also increase the risk of transmitting genetic defects [13].…”
Section: Introductionmentioning
confidence: 76%
“…Sperm disorders in frozen-thawed bull semen, widely used in artificial insemination (AI) technology, confer a risk of impaired fertility in cattle (Bos taurus; BTA). Semen cryopreservation is nonetheless a valuable and effective method for disseminating and preserving superior genetics in livestock production (e.g., [1][2][3][4][5]). It allows the use of AI to increase reproductive efficiency and genetic gain in livestock [6].…”
Section: Introductionmentioning
confidence: 99%
“…On a longer term, these databases may lead to the annotation of genes for multifactorial/polygenic traits or disorders and additionally enable future ranking of embryos for traits based on polygenic risk analysis. While the initiation of human embryo selection based on PGT-P poses several ethical and technical problems 78 82 , the development of PGT-P in horses can be valuable for assessing important equine polygenic disorders like osteochondrosis dissecans 83 85 or insect bite hypersensitivity 86 and traits like performance 87 , 88 , parasite susceptibility 89 or fertility 90 , 91 , for which genome-wide association studies in horses are increasing the knowledge on the heritability and associated SNPs. On the other hand, obtaining materials from family members is straightforward in humans but poses a hurdle for the application of haplotyping-based PGT in the horse industry.…”
Section: Discussionmentioning
confidence: 99%
“…On a longer term, these databases may lead to the annotation of genes for multifactorial/polygenic traits or disorders and additionally enable future ranking of embryos for traits based on polygenic risk analysis. While the initiation of human embryo selection based on PGT-P poses several ethical and technical problems [79][80][81][82][83] , the development of PGT-P in horses can be valuable for assessing important equine polygenic disorders like osteochondrosis dissecans [84][85][86] or insect bite hypersensitivity 87 and traits like performance 88,89 , parasite susceptibility 90 or fertility 91,92 , for which genome-wide association studies in horses are increasing the knowledge on the heritability and associated SNPs. On the other hand, obtaining materials from family members is straightforward in humans but poses a hurdle for the application of haplotyping-based PGT in the horse industry.…”
Section: Discussionmentioning
confidence: 99%